Comparison of four surgical methods for eyebrow reconstruction - Omranifard Mahmood; Koushki A (Indian Journal of Plastic Surgery)
Background: The eyebrow plays an important role in facial harmony and eye protection. Eyebrows can be injured by burn, trauma, tumour, tattooing and alopecia. Eyebrow reconstructions have been done via several techniques. Here, our experience with a fairly new method for eyebrow reconstruction is presented. Materials and Methods: This is a descriptive-analytical study which was done on 76 patients at the Al-Zahra and Imam Mousa Kazem hospitals at Isfahan University of Medical University, Isfahan, Iran, from 1994 to 2004. Totally 86 eyebrows were reconstructed. All patients were examined before and after the operation. Methods which are commonly applied in eyebrow reconstruction are as follows: 1. Superficial Temporal Artery Flap (Island), 2. Interpolitation Scalp Flap, 3. Graft. Our method which is named Forehead Facial Island Flap with inferior pedicle provides an easier approach for the surgeon and more ideal hair growth direction for the patient. Results: Significantly lower rates of complication along with greater patient satisfaction were obtained with Forehead Facial Island Flap. Conclusions: According to the acquired results, this method seems to be more technically practical and aesthetically favourable when compared to others.